Study regarding the knowledge & understanding domain in the physical education classes - Iconomescu Teodora Mihaela; Talaghir Laurentiu-Gabriel; Enache Ion-Sebastian; Rus Cristian-Mihail (SHS Web of Conferences)
The Physical Education (PE) lesson is considered by many researchers to be the main tool that can be used to reduce the sedentary lifestyle of the population. But the most effective way to teach this lesson is still a topic of intense debate among schoolers. The present paper aims to highlight the importance of theoretical knowledge in the educational process in the PE lesson. For this reason, a systematic review was conducted through which a number of 42 papers were identified that met the inclusion criteria. Following the analysis of the papers, the results were reported on three themes: (1) PETE (Physical Education Teacher Education); (2) Curriculum; and (3) Research. The researchers believe that the theoretical contents must be taught to the students in the PE lesson so that they can formulate an answer to the question: “Why should they be physically active in life?". But for this to happen, teachers must be trained in this direction, the curriculum must also contain theoretical content, and researchers must demonstrate the benefits that this knowledge brings in the long term.